Development of Mathematics Learning Model Concept-Based Understanding - Mohamad Rif’at; Sudiansyah Sudiansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is the development of a mathematical learning model based on conceptual understanding. The main research problem: How to develop students' current understanding which tends to turn from factual and procedural knowledge to conceptual knowledge? The purpose of the research is to build and develop the emergence of students' conceptual knowledge, as well as to identify and analyze the lecturer's conceptual knowledge. Data were collected through direct observation in the classroom while learning was taking place in the Mathematics Education Study Program. Observations in three different classes, namely Algebra Class, Calculus Class, and Geometry Class. The display and class discussion were recorded by the researcher, especially on some of the problems that arose. Then the researcher developed a discussion through conceptual questions, which aimed to build conceptual knowledge and simultaneously develop prior knowledge from educators and students. The data recording mechanism is from the classroom so that in the first stage, researchers get a class model in learning or teaching mathematics. From the initial model, the researcher and the class developed conceptual thinking of the problem or problem solving as a form of testing the validity of the model. Testing is carried out primarily to avoid factual and procedural knowledge. The results of this study are the identification of mathematical knowledge in learning and can be known how to work and the way the class thinks as a whole. Overall, an analysis of the concept-based learning model is generated.